DIRECTIONS AND WAYS OF ENSURING CONTINUITY IN TEACHING THE NATIVE LANGUAGE OF PRESCHOOLS AND JUNIOR SCHOOLCHILDREN - Onyshchenko, I.V. (Pedagogy of Higher and Secondary Education, 2009)
In clause (article) pressing questions of training to the native language of the senior preschool children and pupils of younger school are considered . Ways of maintenance of perspectivity to training are offered to language of children of these age categories.